Principles of big data preparing, sharing, and analyzing complex information - Berman, Jules J. (Elsevier, Morgan Kaufmann, 2013)
Helps readers avoid the common mistakes that endanger all Big Data projects. By stressing simple, fundamental concepts, this book teaches readers how to organize large volumes of complex data, and how to achieve data permanence when the content of the data is constantly changing.